Law Enforcement Regarding Human Rights According to Positive Law in Indonesia - Tiara Saskia Maharani (PT. Anagata Sembagi Education, 2024)
This article discusses the importance of recognition and protection of human rights in the Indonesian legal system, focusing on the 1945 Constitution and its amendments, as well as Law No. 39 of 1999. Furthermore, the article highlights the establishment of law enforcement agencies, such as Komnas HAM, as a commitment by the government to ensure justice. The Second Amendment of 2000 strengthened the position of human rights in the hierarchy of national legal norms. This research aims to explore the mechanisms for applying the law to human rights violations and the remedies required in Indonesia. The application of law includes legal groundwork through the Human Rights Court, while remedies involve mechanisms such as peace, consultation, and mediation, which must take into account cultural and social values. With active community support and coordination of relevant institutions, human rights enforcement is expected to remain in line with local and universal values.